Cover Image. Issue 5 (19th October 2020) - Unknown
Abstract : An optical microscope image of the poly(ethylene oxide) precursor material (PEO‐4000) and of the corresponding film are shown in the lower and upper reaches of the image, respectively. By using the green light of a femtosecond laser system, focused on PEO targets, intact polymer molecules are ejected and subsequently deposited on sapphire substrates. In e.10153, Dieter Fischer studies the properties of the obtained PEO films depending on the molecular weight and the deposition temperature, concluding that polymers with a chain length up to around 1 micrometer can be transferred successfully by this method. (doi.org/10.1002/pcr2.10153 ) Abstract : An optical microscope image of the poly(ethylene oxide) precursor material (PEO‐4000) and of the corresponding film are shown in the lower and upper reaches of the image, respectively. By using the green light of a femtosecond laser system, focused on PEO targets, intact polymer molecules are ejected and subsequently deposited on sapphire substrates. In e.10153, Dieter Fischer studies the properties of the obtained PEO films depending on the molecular weight and the deposition temperature, concluding that polymers with a chain length up to around 1 micrometer can be transferred successfully by this method. (doi.org/10.1002/pcr2.10153 )